Physicochemical properties and bioactivity of hydroxyapatite/zirconia biocomposite prepared by ball milling - Mohammaddoost, Fatemeh (2016)
The superior biocompatibility and bioactivity of hydroxyapatite (HA) ceramic has attracted much attention as a substitute material in bone grafting. However, the mechanical properties of HA are low in comparison with cortical bone. Therefore, Zirconia (ZrO2) is a well-known material, which is bioinert material. The effects of Zirconium oxide (ZrO2) additive on the microstructure and physical properties of hydroxyapatite (HA) as well as on the bioactivity were investigated in this study. The HA-ZrO2 powder was derived from natural bovine bone by a high energy milling technique with specified sintering temperature. In the present work, HA-ZrO2 bio ceramic were produced at various sintering conditions (1150, 1200, 1250 and 1300 °C) with different ZrO2 concentrations (0.0, 0.2, 0.4 and 0.8 wt%) in two different milling times (30 min and 1 h), hence the effects of the amount of ZrO2 in the biocomposite on the structure and mechanical properties were investigated. All samples showed HA as a major phase and beta-tricalcium phosphate (β-TCP) and alpha-tricalcium phosphate (α-TCP) phases as a minor phase, which also showed tetragonal zirconia (t-ZrO2) phase. The XRD results showed that the decomposition of HA (amount of β -TCP and α –TCP phases) increased with the increasing amount of additive (ZrO2). Furthermore, the additive inhibited grain growth as a result of a decrease in grain size (as shown in the SEM images). The density was determined by Archimedes method and the results showed that the highest density (2.97 g/cm3) was achieved for a biocomposite that sintered at 1250 C containing 0.2 wt% of ZrO2, for 1 h milling time, which, is consistent with microhardness data. The highest value of microhardness was 286 HV, which was observed for the same sample as the highest density value. Besides that, the density and microhardness values were increased by increasing the milling time from 30 min to 1 h. This could probably be due to the increase of t-ZrO2 by increasing the milling time, which was observed in XRD results. In conclusion, the mechanical properties increased by increasing the milling time from 30 min to 1 h. The in-vitro method was used to test the bioactivity of the biocomposite. For instance, bioactivity was studied by soaking the samples in the SBF solution for two different periods of time, namely 7 and 15 days, followed by the SEM, EDX analysis as well as XRD. The SEM results showed the apatite on the surface of HA-ZrO2 biocomposite on a 7 day growth and when the immersion time increased to 15 days, the growth of apatite on the surface increased more. Other than that, the EDX showed that the covered layer on the surface was P and Ca as well as O. The XRD results showed that the soaked HA-ZrO2 biocomposite composed HA and ZrO2 and no other phases were detected. Also, ZrO2 reduced the dissolution rate of the biocomposite in the SBF. From the findings, we concluded that the addition of ZrO2 to HA increased the mechanical properties and bioactivity of the biocomposite.